The Value of the Relationship in Volunteer Home Support Programs Working with Vulnerable Families. Issue 3 (3rd July 2019) - Dowling, Bronwyn Gai
ABSTRACT: This paper reports on a program evaluation project that included interviews with 35 parents from high-risk backgrounds who received home volunteer support as part of the Dalwood Volunteer Home Support Program. It provides insight into the meaning and value parents attach to the volunteer relationship. The evaluation findings suggest that home volunteer support was associated with parent perception of increased wellbeing, decreased social isolation, and an improved relationship with their child. The results also suggest that parents perceived their relationship with their volunteer as significant in providing a secure base relationship. IMPLICATIONS: Further research is needed to develop an evidence-base for Volunteer Home Support Programs for vulnerable families of young children. Social workers are well placed to further explore this model of family support, the value of the unique parent–volunteer relationship, and the impact on the relational health of vulnerable children and parents.